A cationic fcu-lanthanide MOF enhances the uptake of iodine vapour at room temperature. Issue 91 (28th October 2022) - Zwanziger, Clara; do Pim, Walace D.; Kitos, Alexandros A.; Ovens, Jeffrey S.; Pallister, Peter J.; Murugesu, Muralee
Abstract : The cationization of a RE fcu MOF using the asymmetric ligand exchange (ALE) methodology was found to be beneficial for boosting iodine vapor uptake, a proof-of-concept for the confinement of polarizable and anionic species in the pores of the MOF. Abstract : The first example of a cationic cluster-based fcu –lanthanide metal–organic framework (MOF) bearing an asymmetric linker, herein named UOTT-4, has been designed and fully characterized. Compared to its rare–earth (RE) anionic counterpart (RE-UiO-66), UOTT-4 was found to significantly improve the performance towards adsorption of iodine vapour at room temperature, opening avenues for the design of the next-generation cationic porous materials for the beneficial uptake and confinement of target molecules.